STRUKTUR KEPRIBADIAN CAKRA DALAM NOVEL NOT ME KARYA CAHYA MAHARANI - Haerunnisa; La Ode Sahidin; La Ode Akhiri Zulzaman (PT. CASA CENDEKIA MEDIA, 2025)
This study aims to examine the personality structure of Cakra in the novel Not Me by Cahya Maharani reviewed from Jung's archetype. The expected benefits of this study are that the results of this study are expected to broaden the author's knowledge and insight in analyzing the personality structure of characters in novels, are expected to provide understanding to readers so that they are always active in reading and exploring the personality structure of characters presented in literary works, and are expected to be a reference for other researchers who research similar objects. The method used is a qualitative descriptive method. The data source for this study is the novel Not Me by Cahya Maharani with a total of 300 pages published by PT Moka Media in 2021. Data collection was carried out using analytical reading techniques. This study uses a literary psychology approach. The results of this study indicate that the personality structure of Cakra in the novel Not Me by Cahya Maharani reviewed from Jung's archetypes, namely: (1) persona in the form of encouragement, strong image, cheerful child; (2) anima in the form of caring, empathy, compassion, attention, support, responsibility, sincerity, nurturing, and affection; (3) shadow in the form of trauma, wounds, loneliness, bullying, lack of self-confidence, darkness, fear, helplessness, loss of freedom, feeling insecure, anxiety, feeling left out, sadness, difficulty accepting oneself, painful memories, avoidance, anger, rejection, doubt, fragility, and hallucinations; (4) self in the form of reflection, acceptance, self-confidence, honesty, compassion, strong independence, awareness, empathy, and balance.